All Petrarch’s Fault: The Idea of a Renaissance - Petrina, Alessandra (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2020)
This article discusses the meaning of the term Renaissance and its application to the cultural and literary sphere, discussing its early definitions on the part of scholars such as Jules Michelet, Jacob Burckhardt, and Johan Huizinga, as well as its etymology, in the context of the investigation of other keywords such as Humanism and Middle Ages. It then focuses on the latter term, Middle Ages, by considering its first creation, and its use on the part of a proto-humanist such as Petrarch. In the discussion of the reception of these terms on the part of scholarship, it also proposes a new meaning for these terms. Keywords: Renaissance, Early Modern, Middle Ages, Humanism, Petrarch